HYPONATREMIA AS A PROGNOSTIC INDICATOR IN LOWER RESPIRATORY TRACT INFECTIONS IN CHILDREN ADMITTED IN PAEDIATRIC INTENSIVE CARE UNIT: Hyponatremia as Prognostic Indicator in RTI - Hamid, Naila; Shafique, Muhammad Faisal; ., Qamar-uz-Zaman; Niaz, Hafza (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study the serum sodium levels in patients of lower respiratory tract infections admitted in the paediatric intensive care unit with their prognosis. Study Design: Prospective observational study. Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi, from Jan to Jun 2018. Methodology: Eighty patients suffering from lower respiratory tract infections who were admitted to the paediatric intensive care unit were selected at consecutive sampling. The outcome was recorded in the form of discharge or mortality. Serum sodium was done at the time of admission and then periodically after every 24-48 hours. The Association of patients’ serum sodium with their prognosis was studied using chi-square test and p-value was calculated. Results: A total of 80 patients were enrolled in our study out of which 50 (62.50%) were males and 30 (37.50%) were females. Out of the total, 48 patients suffered from hyponatremia. These 48 patients had a mean serum sodium concentration of 131.24 ± 3.31 mEq/L. The mean age of patients suffering from hyponatremia was 5.78 ± 3.4 years. Mortality occurred in 5 (80.12%) of patients suffering from severe hyponatremia. Conclusion: There was a significant association of hyponatremia with mortality in children admitted in paediatric intensive care settings with lower respiratory tract infections. Therefore, proper management hence correction of serum sodium levels can improve survival in, particularly children admitted in a pediatric intensive care setting.